Qualitative research and evaluation in physical education and sport pedagogy - Richards, Kevin Andrew; Hemphill, Michael A.; Wright, Paul M. (Professor of kinesiology and physical education)
"A practically-focused introductory qualitative methods text specific to physical education and activity to guide graduate students and early career researchers through the design, conduct, and reporting of qualitative research studies with specific references to the challenges and possibilities of the field"